Literariness and Ideology in Malaysian Newspaper Advertisements in English: Some Case Studies - Rajaram, Devan Vengadasalam (SARE: Southeast Asian Review of English, 2017)
This study identifies elements of literariness, and ideology that are used in advertisements found in two Malaysian newspapers. The New Straits Times and The Star. It examines how ideologies are transmitted in the messages of the advertisers. To achieve this purpose, this study focuses on how elements of literariness are used as the medium of transfer of ideology in the process of transmitting the advertiser's message. Criteria that are analysed include an interaction of different levels leading to semantic density, polysemy, re-registration, discourse patterning, dispaced interaction and medium dependence. The framework used in this study is Roland Carter's criteria of literariness (1977).